2020
DOI: 10.1177/2325967120918383
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport After Hip Arthroscopy for Femoroacetabular Impingement Syndrome in NCAA Division I Athletes: Experience at a Single Institution

Abstract: Background: The rate of return to sport after surgical treatment of femoroacetabular impingement (FAI) syndrome (FAIS) has been studied in high-level athletes. However, few studies examining this rate have focused exclusively on National Collegiate Athletic Association (NCAA) Division I athletes. Purpose: To evaluate the return-to-sport rate after hip arthroscopy for FAIS and to examine the influence of sport type on the clinical presentation of FAIS in collegiate athletes. Study Design: Case series; Level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
(49 reference statements)
1
12
0
Order By: Relevance
“…3,28 While FAIS reduces patients' ability to perform activities of daily living or participate in sports, 28 arthroscopic management results in improved functional patient-reported outcomes (PROs) and return to sports at midterm followup. 4,5,22,26,35 Recent studies have reported superior outcomes after hip arthroscopy as compared with nonoperative management, with patients who undergo arthroscopy being more likely to achieve the minimal clinically important difference for several validated PRO scores. 10,11 A significant proportion of patients with FAIS have psychiatric disorders, with up to 35% of patients reported to have a diagnosis of depression or anxiety before elective hip arthroscopy.…”
mentioning
confidence: 99%
“…3,28 While FAIS reduces patients' ability to perform activities of daily living or participate in sports, 28 arthroscopic management results in improved functional patient-reported outcomes (PROs) and return to sports at midterm followup. 4,5,22,26,35 Recent studies have reported superior outcomes after hip arthroscopy as compared with nonoperative management, with patients who undergo arthroscopy being more likely to achieve the minimal clinically important difference for several validated PRO scores. 10,11 A significant proportion of patients with FAIS have psychiatric disorders, with up to 35% of patients reported to have a diagnosis of depression or anxiety before elective hip arthroscopy.…”
mentioning
confidence: 99%
“…Injury data were prospectively collected by athletic trainers using a standardized system, which has been used in previous epidemiological studies. 18 , 28 , 34 , 35 This study was determined to be exempt from institutional review board approval.…”
Section: Methodsmentioning
confidence: 99%
“…The minimally invasive nature and advances in hip arthroscopic techniques have provided athletes a relatively rapid to return to sports at their preinjury levels. 2,9,30,31,36,37,38 Furthermore, return-to-play rates for professional and elite athletes have ranged from 83% to 100% across multiple sports, such as ice hockey, soccer, football, basketball, baseball, and golf for at least 1 season. 5,8,12,23,27,29,35 The purposes of this study were to determine the return-to-sports rate of elite skiers and snowboarders who have undergone hip arthroscopic surgery for FAI and to assess hip-related outcomes at a minimum 2-year follow-up.…”
Section: -In-5mentioning
confidence: 99%
“…The minimally invasive nature and advances in hip arthroscopic techniques have provided athletes a relatively rapid to return to sports at their preinjury levels. 2,9,30,31,36,37,38 Furthermore, return–to–play rates for professional and elite athletes have ranged from 83% to 100% across multiple sports, such as ice hockey, soccer, football, basketball, baseball, and golf for at least 1 season. 5,8,12,23,27,29,35…”
mentioning
confidence: 99%